2020
DOI: 10.1002/pam.22238
|View full text |Cite
|
Sign up to set email alerts
|

Child Support and the Affordable Care Act's Medicaid Expansions

Abstract: A quickly developing literature has shown that the Affordable Care Act's (ACA) Medicaid expansions have improved health insurance coverage, health, and financial well‐being among low‐income adults without dependent children. This population includes noncustodial parents. With substantial overlap in the population that is typically obligated to pay child support and the population that has strongly benefited from the expansions, there may be potential implications for child support enforcement. In this paper, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…First, we found that the ACA Medicaid expansions for low-income parents between 2016 and 2019 increased children's public health insurance coverage by 5.6 percentage points (about 8.5 percent). Our findings are consistent with past literature on the welcome mat effects of public health insurance expansions for adults for already eligible children (Hudson & Moriya, 2017;2020). Specifically, to put this in context with prior work, using data from the American Community Survey (ACS), Hudson & Moriya (2017) estimate a welcome mat effect of 5.7 percentage points (8.1 percent) for children as a result of the ACA expansions to adults.…”
Section: Discussionsupporting
confidence: 87%
“…First, we found that the ACA Medicaid expansions for low-income parents between 2016 and 2019 increased children's public health insurance coverage by 5.6 percentage points (about 8.5 percent). Our findings are consistent with past literature on the welcome mat effects of public health insurance expansions for adults for already eligible children (Hudson & Moriya, 2017;2020). Specifically, to put this in context with prior work, using data from the American Community Survey (ACS), Hudson & Moriya (2017) estimate a welcome mat effect of 5.7 percentage points (8.1 percent) for children as a result of the ACA expansions to adults.…”
Section: Discussionsupporting
confidence: 87%
“…The literature on Medicaid expansion's impact on patients finds that health care reform under the ACA, especially states’ Medicaid expansion, improves patients’ access to health care and health outcomes, and the impact is more pronounced for low-income or vulnerable groups (Sommers et al 2015; McMorrow et al 2015; Wherry and Miller 2016; Frean et al 2017; Soni et al 2017; Wehby and Lyu 2018; Denham and Veazie 2019; Hamersma et al 2019). The existing research also demonstrates that Medicaid expansion has positively affected patients’ utilization of services, the affordability of care (Kirby and Vistnes 2016; McMorrow et al 2015; Soni et al 2017), child support (Bullinger 2021), reduced crime (Vogler 2020), mortality (Borgschulte and Vogler 2020), and, in some expansion states, has positive economic effects on employment, personal income savings, and state tax revenues (Ayanian et al 2017; Heim and Yang 2017). 1…”
Section: Literature Reviewmentioning
confidence: 99%
“…These decisions have substantially changed frontline health care providers’ external market and policy environments. Since the passage of the ACA, there has been an outpouring of empirical studies examining the effects of state Medicaid expansion (Haeder 2020), most of which find positive short-term impacts on insurance coverage (Courtemanche et al 2017; Sommers 2017 a ), population health outcomes (Simon, Soni and Cawley 2017; Sommers 2017 b ; Borgschulte and Vogler 2020), and broader economic outcomes (Mathur, Slavov and Strain 2016; Heim and Yang 2017; Kaestner et al 2017; Leung and Mas 2018; Gangopadhyaya and Garrett 2020; Vogler 2020; Bullinger 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the expansions have been linked to adults’ physical health, 14 , 31 including parents, 26 , 32 and behavioral health. 33 - 36 Bullinger 37 also finds improvements in child support payments. Together, this literature implies that the expansions created more financial security and stability among low-income parents.…”
Section: Introductionmentioning
confidence: 96%